An Examination of Latinx LGBT Populations Across the United States : Intersections of Race and Sexuality - Pastrana, Jr., Antonio (Jay); Battle, Juan; Harris, Angelique (Palgrave Macmillan US : Imprint: Palgrave Pivot, 2017)
This book utilizes personal narratives and survey data from over 1,100 respondents to explore the diversity of experiences across Latinx LGBT communities within the United States, including Puerto Rico. The authors document and celebrate many of the everyday strengths and strategies employed by this extraordinary population to navigate and negotiate their daily lives. Antonio (Jay) Pastrana, Jr. is an Associate Professor at John Jay College of Criminal Justice, CUNY, USA Juan Battle is a Professor of Sociology at the Graduate Center, CUNY, USA Angelique Harris is an Associate Professor of Sociology and Director of the Center for Gender and Sexualities Studies at Marquette University, USA.- Resumé vydavatel
Keywords: sexuální menšiny -- Spojené státy americké; etnické skupiny -- Spojené státy americké; Latinoameričané -- Spojené státy americké; sexual minorities -- United States; ethnic groups -- United States; Latin Americans -- United States; elektronické knihy; kolektivní monografie; electronic books; collective monographs